Stable genius: Estimating the 'Trump effect' on the US economy - Benjamin Born; Gernot Müller; Moritz Schularick (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2018)
Growth and employment in the US have been robust over the past 18 months, and President Trump frequently takes personal credit for these trends. This column explores how the US economy would have evolved without Trump. An analysis shows no difference between the post-election performance of the US economy under Trump and a synthetic 'doppelganger' US economy without Trump, suggesting that there has been no 'Trump effect'.
Keywords: 330